2017
DOI: 10.1016/j.crci.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Controlling phenolic hydrodeoxygenation by tailoring metal–O bond strength via specific catalyst metal type and particle size selection

Abstract: Experimental and theoretical studies of hydrodeoxygenation (HDO) of m-cresol show that on metals of low oxophilicity, such as Pt or Pd, the direct CeO bond cleavage is not possible. Therefore, HDO requires an indirect pathway via tautomerization. In contrast, on metals of higher oxophilicity, such as Ru or Rh, the direct CeO bond cleavage is possible and toluene can be directly obtained from m-cresol. These studies show that the HDO activity correlates directly with the metal oxophilicity, which in turn depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…We also considered the possibility that HDO of m -cresol over Pt iso could be hindered by the difficulty in performing C–O bond scission over these sites. In previous studies, we have shown that the barrier for the kinetically relevant C–O scission step in HDO correlates strongly with the oxygen binding energy of the metal . Therefore, weaker interaction between Pt iso and cresol could render it inactive for catalyzing this reaction step.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We also considered the possibility that HDO of m -cresol over Pt iso could be hindered by the difficulty in performing C–O bond scission over these sites. In previous studies, we have shown that the barrier for the kinetically relevant C–O scission step in HDO correlates strongly with the oxygen binding energy of the metal . Therefore, weaker interaction between Pt iso and cresol could render it inactive for catalyzing this reaction step.…”
Section: Resultsmentioning
confidence: 96%
“…In previous studies, we have shown that the barrier for the kinetically relevant C−O scission step in HDO correlates strongly with the oxygen binding energy of the metal. 23 Therefore, weaker interaction between Pt iso and cresol could render it inactive for catalyzing this reaction step. We have previously shown that the binding energy of small adsorbates over stable Pt iso sites is significantly lower than it is over extended Pt surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For HDO of phenolics, a few pioneering works devoted to the effect of metal particle size have been reported, with particular attention paid to the noble metal based catalysts. Newman et al performed HDO of phenol at 300 °C and 600 psi H 2 and 50 psi N 2 over two Ru/TiO 2 samples . They reported that benzene selectivity on Ru/TiO 2 with Ru particle size of 1.5 nm (86% selectivity at 12% conversion) is dramatically higher than that with Ru particle size of 33 nm (18% selectivity at 4% conversion).…”
Section: Introductionmentioning
confidence: 99%
“…Since the reducible TiO 2 and ZrO 2 supports may participate in the deoxygenation, it is difficult to draw a clear conclusion on the effect of metal particle size. Recently, Resasco et al reported HDO of m -cresol in a pulse reactor over two Rh/SiO 2 catalysts with Rh particle sizes of 4 and 2 nm, achieved by varying Rh loadings . The turnover number (TON) for toluene formation was moderately improved when Rh size was reduced from 4 to 2 nm, while the TON for the formation of cracking products of C2–C6 was found to be little affected by the change of size.…”
Section: Introductionmentioning
confidence: 99%